The (Bio)Chemistry of Soil Humus and Humic Substances: Why Is the “New View” Still Considered Novel After More Than 80 Years? - Baveye, Philippe C.; Wander, Michelle (Frontiers in Environmental Science, 2019)
Three years ago, a novel “soil continuum model” was proposed, in which soil organic matter was suggested to be of heterogeneous composition and to consist of a continuum of organic fragments of all sizes. A search of the literature reveals that this model is identical to several similar conceptualizations proposed about 15 years ago, and that it corresponds closely with the description of humic substances given in Waksman’s (1936) remarkably thorough book on the topic, that also emphasized the intimate connections existing between humic substances and soil microorganisms. Several historical reasons, reviewed in this Perspective article, may explain why Waksman’s viewpoint might still be considered novel more than 80 years later. Here we argue that the key reason for the agonizingly slow rate of progress in the field is linked to the extreme compartmentalization of research and education in soil science, which has been organized along distinct subdisciplines, with the result that interdisciplinary efforts that are desperately needed to understand the dynamics of soil humic substances are very hard to launch. To meet growing demands on soils we need to understand the mechanisms that underpin their many functions. To gain this understanding and finally make badly needed progress, we must reorganize funding and educational efforts to support exploration of “Waksman’s frontier”, which includes the microscale where the microbial, physical and biochemical processes governing organic matter turnover occur.